Biologist Petre Jitariu Member of the Romanian Academy, President of the Iași Branch of the Romanian Academy (1974–1989) - Elena Niculae-Grigorescu; Laura Mocanu (Memoirs of the Scientific Sections of the Romanian Academy)
Fifty years after being elected President of the Romanian Academy, Branch of Iaşi, and thirty-five years after his passing away, the Academy member Petre Jitariu is still present in the memory of the academic and scientific community. The article approached Petre Jitariu’s life, professional becoming, scientific contribution, as well as the institutional growth of the Iași Branch of the Romanian Academy under his administration.